1997
DOI: 10.1002/(sici)1097-0215(19970620)74:3<275::aid-ijc7>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin expression in human epithelial ovarian cancer and normal ovary

Abstract: The ovarian surface epithelium (OSE) is the origin of the majority of human ovarian cancers. These adenocarcinomas are characterized by initial local growth followed by spreading into the peritoneal cavity at later stages of tumor progression. The cell-adhesion molecule E-cadherin (E-cad) plays an important role in maintaining tissue integrity. Disappearance or impaired function of E-cad have often been associated with tumor formation and invasion in vivo and in vitro. The cell-specific expression of E-cad was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 21 publications
(44 reference statements)
8
104
0
1
Order By: Relevance
“…In fact, both Nand E-cadherin can reduce or block the transcriptional activity of b-catenin/Lef1, relocate b-catenin to the cell border and inhibit the degradation of b-catenin (Sadot et al, 1998). We and others have earlier demonstrated that E-cadherin is induced during the progression of ovarian epithelial tumours (Sundfeldt et al, 1997;Auersperg et al, 2001). The elevated expression of E-cadherin in ovarian cancer could increase binding of b-catenin to the plasma membrane.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, both Nand E-cadherin can reduce or block the transcriptional activity of b-catenin/Lef1, relocate b-catenin to the cell border and inhibit the degradation of b-catenin (Sadot et al, 1998). We and others have earlier demonstrated that E-cadherin is induced during the progression of ovarian epithelial tumours (Sundfeldt et al, 1997;Auersperg et al, 2001). The elevated expression of E-cadherin in ovarian cancer could increase binding of b-catenin to the plasma membrane.…”
Section: Discussionmentioning
confidence: 97%
“…The downregulation of cadherins or dysfunction of the cadherincatenin complex has been noted in different types of tumours. In the human ovary, neuronal (N) cadherin, but not epithelial (E) cadherin, is expressed in the normal ovarian surface epithelium (OSE) (Sundfeldt et al, 1997;Auersperg et al, 2001). However, Ecadherin is upregulated in inclusion cysts of the normal ovary and in ovarian tumours with invasive capacity (Sundfeldt et al, 1997;Auersperg et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In tissue culture, OSE cells express epithelial markers including keratin, desmosomes, tight junctions, laminin, basement membrane type IV collagen and apical microvilli, as well as mesenchymal markers such as vimentin and interstitial collagen types I and III [13,14]. The mesodermally derived OSE expresses unusually low levels of the epithelial cell-cell adhesion molecule E-cadherin [13,15], with expression limited to inclusion cysts or deep clefts [16] where early malignant changes are believed to occur [16,17]. In contrast to other epithelia, OSE epithelial integrity is maintained primarily by neural-(N)-cadherin, consistent with the epithelial-mesenchymal phenotype of this tissue [13,[18][19][20].…”
Section: Normal and Neoplastic Ovarian Epitheliummentioning
confidence: 99%
“…E-Cadherin-An unique feature of EOC is that E-cadherin becomes more abundant in primary differentiated ovarian carcinomas [16,18,20,51,53,[56][57][58][59], with all histotypes displaying strong immunoreactivity. Our data demonstrate positive E-cadherin staining in 86% of tumors analyzed (n=146) with strong immunoreactivity in 73%, consistent with a gain of epithelial phenotype [ Table 1, Fig.…”
Section: B Cadherin Expression In Eocmentioning
confidence: 99%